Investigating Effect of Premarital Health Counseling on Females' Awareness Towards Breast and Cervical Cancer - ES HajiKazemi; R. Mohammadi; S. Nikpour; F. Hosseini; A. Meamarian (Iran University of Medical Sciences, 2006)
Premarital health counseling for couples, especially in females is very important in community's health. In the premarital counseling, females are educated regarding reproductive health, such as methods of prevention of breast and cervical cancer that helps to family health promotion. The aim of this study, was to determine the effect of premarital health counseling on the females' awareness towards methods of prevention of breast and cerviced cancers.   This study was a quasi experimental design. The aim of the study was to determine the difference of the subjects' awarness about methods of prevention of breast and cervical cancer at preintervention and post intervention. The mean & standard deviation of the achieved scores related to the awarenss were calculated. The sample size was 600 subjects who were attending in premarital health counseling program in selected health centers. The sampling method was consequence and the study tool was a questionnaire.   The study finding, showed that the mean and standard deviation of samples' age was 21.82 ± 3.94 and 47.4%. The majority of the subjects had a level of diploma degree in education and, 76.6% were housewives. The differences between the mean of their scores of the subjects' awarences in the two groups (who participated in the counseling and who did not) were significant (P<0.0001).   Considering the importance of prevention methods of breast and cervical cancer, the researchers suggest to conduct a prospective study for assassing the effect of premarital health counseling program on females' practice. The study findings showed, a high efficacy of the premarital counseling regarding the subjects awareance about prevention methods of breast and cervical cancer. Thus, the researchers recommend further studies of the efficiency of the premarital counseling on long-term outcomes among females, attending premarital counseling.